2014
DOI: 10.1016/j.jcm.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bell's Palsy Using Monochromatic Infrared Energy: A Report of 2 Cases

Abstract: Objective: The purpose of the study is to describe the use of monochromatic infrared energy (MIRE) therapy in the management of 2 patients with Bell's palsy. Clinical features: Two patients presented to a chiropractic clinic with Bell's palsy that was diagnosed by a medical physician. Both patients were treated using MIRE. The acute patient was a 32-year-old male. He presented with left facial palsy 1 day before the consultation. He was unable to puff the left cheek and close the left eyelid. He had difficulty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…A search of PubMed, Google Scholar, and hand-searching of a recent review paper [ 28 ] on June 3, 2022 identified 12 case reports in which a chiropractor successfully treated Bell’s palsy using spinal manipulation [ 29 – 37 ]. Of these cases, including the current case (ie, a total of 13 cases), the mean patient age was 36 (SD) ±14 years and the mean duration of symptoms was 13 (SD) ±19 months, with 54% of patients being female ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A search of PubMed, Google Scholar, and hand-searching of a recent review paper [ 28 ] on June 3, 2022 identified 12 case reports in which a chiropractor successfully treated Bell’s palsy using spinal manipulation [ 29 – 37 ]. Of these cases, including the current case (ie, a total of 13 cases), the mean patient age was 36 (SD) ±14 years and the mean duration of symptoms was 13 (SD) ±19 months, with 54% of patients being female ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among cases reporting the location of spinal manipulation (11/13), this therapy was administered to the cervical spine in each case (11/11, 100%), and to the upper cervical spine in 8/11 (73%) of cases. Select patients received additional treatments, such as acupuncture [ 29 , 37 ], infrared light [ 29 , 30 ], and electric stimulation [ 31 , 33 , 34 ]; therefore, the positive response to treatment could have been related to a combination of therapies rather than spinal manipulation alone.…”
Section: Discussionmentioning
confidence: 99%
“…(24) MIRE therapy in which infrared light of wavelength 890nm, is used on the area anterior and posterior to the ear, the temporal and lower jaw area of the affected side for the half-anhour cycle. (25,26) When a case of facial palsy comes to a dentist,the following can be followed: thorough history taking and physical examination to exclude all possible causes for facial palsy, routine laboratory testing, and diagnostic imaging should be avoided if it is a new case of Bell's palsy, oral steroids (prednisolone) can be given within 72 hours of the appearance of symptoms,(For adults who come within 72 hours of onset treatment recommendations are " Corticosteroids: Prednisone 50 mg orally daily for 5 days, followed by 10 mg less each day for 5 days, Prednisolone 50 mg OD for 10 days, Antivirals: Valacyclovir 1 g TID for 7 days, Acyclovir 400 mg OD five times daily for 7 days)." (12) The basic treatment is neuromuscular re-education training.…”
Section: Discussionmentioning
confidence: 99%
“…The electronic search and screening of titles and abstracts identified nine potentially relevant studies; they were retrieved and considered for inclusion [52][53][54][55][56][57][58][59][60]. Of these studies, five satisfied the eligibility criteria and were included in the review [52][53][54][55][56].…”
Section: Study Selectionmentioning
confidence: 99%